The Green Energy Sector - Nodoushani, Omid; Van den Abbeele, Isaline; Stewart, Carol (Competition Forum, 2015)
Thinking "Green" has become a significant economic trend lately. This research paper offers a better understanding of the background facts of the current hype surrounding "Green Energy." First, the problem of global warming is investigated. Europe has taken a lead role in the fight against global warming in order to meet their objective of 20% renewable energy production by 2020. Many possibilities exist to transform raw biomass into bioenergy fuels, which can then be used for specific energy production purposes: electricity production, warming or transport. Biodiesel, bioethanol, biogas and many other fuels can be produced from biomass.
Num Pages: 6 Place: Indiana, United States
Keywords: Alternative energy; Alternative energy sources; Biomass; Carbon dioxide; Chlorofluorocarbons; Climate change; Energy industry; Environmental impact; Global warming; Greenhouse effect; Greenhouse gases; Nobel prizes; Renewable resources; Studies; Temperature; Trends; dept.mgt

The Multidimensional Work Motivation Scale: Validation evidence in seven languages and nine countries - Gagné, Marylène; Forest, Jacques; Vansteenkiste, Maarten; Crevier-Braud, Laurence; van den Broeck, Anja; Aspeli, Ann Kristin; Bellerose, Jenny; Benabou, Charles; Chemolli, Emanuela; Güntert, Stefan Tomas; Halvari, Hallgeir; Indiyastuti, Devani Laksmi; et al. (European Journal of Work and Organizational Psychology, 2015)
Self-determination theory proposes a multidimensional conceptualization of motivation comprising autonomous and controlled forms. Whereas autonomous motivation relates positively to individuals’ optimal functioning (e.g., well-being, performance), controlled motivation is less beneficial. To be able to use self-determination theory in the field of organizational behaviour, the Multidimensional Work Motivation Scale was developed and tested using data from 3435 workers in seven languages and nine countries. Factorial analyses indicated that the 19-item scale has the same factor structure across the seven languages. Convergent and discriminant validity tests across the countries also indicate that the psychological needs for autonomy, competence, and relatedness as well as the theoretically derived antecedents to work motivation (e.g., leadership and job design) are predictably related to the different forms of motivation, which in turn are predictably related to important work outcomes (e.g., well-being, commitment, performance, and turnover intentions). Implications for the development of organizational research based on self-determination theory are discussed.
_eprint: https://doi.org/10.1080/1359432X.2013.877892
Keywords: Autonomous motivation; Controlled motivation; Cross-cultural; Extrinsic motivation; Intrinsic motivation; Self-determination theory; Validation; Work motivation; dept.mgt

Genetically engineered food and genetically modified organisms - Nodoushani, Omid; Sintay, Jayme; Stewart, Carol (Competition Forum, 2015)
Keywords: dept.mgt; peer-reviewed

Linking Leadership Behaviors and Information Exchange to Improve Supply Chain Performance: A Conceptual Model - Birasnav, M.; Mittal, Rakesh; Loughlin, Selene (Global Journal of Flexible Systems Management, 2015)
Organizations striving to improve cycle time concentrate on developing long-term relationship with suppliers. In order to support organizational efforts, this study develops a conceptual model that explores the relationships among leadership behaviors, relational commitment and trust, information exchange, and cycle time. Although the supply chain management literature mentions leadership behavior in the context of supply chain, there are no studies that examine the impact of leadership behaviors on cycle time. This study proposes that transformational and transactional leadership behaviors of buyers increase the flow of information to suppliers directly as well as indirectly through relational commitment and trust, and these relationships also influence cycle time. However, it also proposes that the impact of transformational leadership behaviors on relational commitment and trust and information exchange is stronger than the impact of transactional leadership behaviors. Additionally, both uncertain environment and supplier base have potential to play moderation roles in the relationship between transformational leadership and relational commitment and trust and between transformational leadership and information exchange.
Keywords: Cycle time; Information exchange; Relational commitment; Relational trust; Supplier base; Transactional leadership; Transformational leadership; dept.mgt; peer-reviewed

Bankruptcy Law and Practice - J.D, Grace A. Luppino; J.D, Robert A. Smith (Pearson, 2015)
Keywords: dept.mgt

Sustainability and stratified noncompliance in the pharmaceutical industry - Page, Robert A.; Cyr, Danielle M.; Richardson, Anthony S. (Journal of International Business Disciplines, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

The Risks and Rewards of Computing Everywhere for Small Business Entrepreneurs. - Bassett, Richard A.; Richardson, Anthony S.; Page, Robert A. (Issues in Information Systems, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed